Case reportConglobate acne in a pregnant woman – an important therapeutic problem. A case report - Kacalak-Rzepka, Anna; Bielecka-Grzela, Stanisława; Królicki, Andrzej; Maleszka, Romuald (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
A case of a 29-year-old pregnant woman suffering from conglobate acne that appeared in the 1st trimester is presented. The influence of pregnancy on the course of acne as well as limitation of anti-acne treatment is discussed. The severe course of acne in this patient required systemic antibiotic treatment followed by laser therapy to correct post-inflammatory lesions.